MINERAÇÃO DE DADOS DE IMAGENS OBTIDAS COM AERONAVE REMOTAMENTE PILOTADA PARA ESTIMATIVA DE PRODUTIVIDADE DO TRIGO - Gerke, Tiago (2017)
Wheat cultivation plays an important role to Brazil and the world economic development, as well as in the human diet. The wheat Brazilian production is insufficient to meet the national demand, making research needed in order to improve the yield of this cereal. The goal of this work was to estimate wheat yield, searching for a predictive model through the data mining techniques, with data obtained from high spatial resolution images collected by unmanned aerial vehicles (UAV). The work was carried out in two experimental areas at Ponta Grossa city, Parana state, where for each area eight images were taken, at different culture development stages, with spatial resolution of 3.4cm/px and two images with resolution 10cm/px and 20cm/px, using an eBee UAV with an RGB and a NIR camera. The image processing was done with the Pix4D software, and resulted in an orthomosaics with reflectance values at different wavelengths: Red, Green and Blue, from the RGB camera and Red, Greed and NIR from the NIR camera, besides an image with NDVI values obtained from the arithmetic of NIR and Red wavelengths. The georeferencing correction of each orthomosaic and the extraction of the reflectance values were done with Quantum GIS geographic information system (GIS). From the extracted reflectance values, databases in different proportions (10%, 20%, 40%, 70% and 100%) were created for data mining, using the SMOReg algorithm, based on a support vector machine (SVM) for regression (SVR). The georreferencing correction using 10 control points provided ortomosaics with mean square error (RSME) of distance of 0.35m, which did not show significant difference compared to the correction with 5 control points (RMSE = 0.38m). The reflectance values were different for each study area, making it difficult to indicate better periods for estimating wheat yield. The highest correlation were obtained with data from RGB camera images, followed by the NIR and NDVI camera, with correlations of 0.6168,0.5423 and 0.5324, respectively. The amount of information extracted from the images, reflected in the proportion of the databases, was not significant to generated predictive models, as well as in the correlation indexes, which were statistically the same. Better correlation indices were obtained from the data extracted from the images with spatial resolution of 20cm/px, which suggests that high spatial resolution images may not be adequate for wheat yield estimation.